Fair value accounting in South African banks : financial stability implications - De Jager, Phillip (Department of Finance and Tax, 2015)
This article-based thesis consists of three main papers that examine the use of fair value accounting in banks and how it can influence behaviour with systemic effects; this helps in understanding the role of fair value accounting in the global financial crisis. The examination consisted of two parts. The first part was the investigation of how fair value accounting was actually used by South African banks. The second part was the development of an analytical model that links together fair value accounting, bank capital regulation and economic outcomes. The South African case study was further divided into two parts. In the first part, a comparative design was used to investigate in detail how fair value accounting was implemented by two South African banks and what their motivations were. The second part sought to answer the question: did South African banks pay out higher dividends based on risky fair value accounting gains? The South African evidence indicates that fair value accounting materially impacts the profit and loss and the regulatory capital of banks. This component of regulatory capital proved to be risky. Dangerous pay-outs resulted from the increase in profits and bank assets grew the most during the period of risky capital formation. It was found that the use of a stock-flow consistent model of the economy was a commonality amongst those that predicted the global financial crisis. A stock-flow consistent model was shown to be descriptive of the South African evidence. The model showed fair value accounting to be at the centre of feedback processes that can weaken the banking system during the economic upswing. The study concludes that fair value accounting is central in processes that weaken the banking system during an economic upswing and thus demonstrates why the current call for prudent accounting in banks is justified. The study expands on current literature in a number of ways. It adds to the literature that fair value accounting is procyclical by demonstrating that this effect is not constant throughout the cycle and is more problematic during the upswing; this differs from the usual argument that fair value accounting accelerates the downturn. The South African empirical evidence showed that fair value accounting for available-for-sale assets is not the only avenue for fair value accounting to be dangerous; fair value accounting adjustments through profit and loss should also be monitored. The analytical model as well as the South African empirical evidence contradicts the common argument that the fair value measurement of financial instruments must be pervasive in a bank and banking system to be dangerous. The South African empirical evidence shows that fair value accounting must be considered a possible avenue of earnings or capital management in banks.